2000
DOI: 10.1111/j.1528-1157.2000.tb02169.x
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate as an Inhibitor of Carbonic Anhydrase Isoenzymes

Abstract: Summary: Purpose: This study investigated the effectiveness of topiramate (TPM) as an inhibitor of six isozymes of carbonic anhydrase (CA). Methods: The inhibition constants (Ki) of TPM and acetazolamide (AZM) for CA I, CA II, CA III, CA IV, CA V, and CA VI were determined for human (HCA), rat (RCA), or mouse (MCA). The activity of CA was studied by using purified isozymes, erythrocytes, subcellular fractions of kidney or brain, and saliva, and was assayed at 37°C or 25°C by 18O mass spectrometry and/or by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
161
1
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(167 citation statements)
references
References 18 publications
1
161
1
3
Order By: Relevance
“…Fifth, HCO 3 − dependent depolarization may lead to the activation of voltage-gated Ca 2+ channels (Autere et al, 1999). In line with this view, it has been reported that antiepileptic drugs such as topiramate inhibit the cytosolic carbonic anhydrase (Dodgson et al, 2000) thus decreasing or abolishing GABA A receptor-mediated depolarizing responses (Herrero et al, 2002). In addition, it has been proposed that inhibiting NKCC1 with bumetanide can reduce and even abolish seizures in rodent models of neonatal seizures (Dzhala et al, 2005(Dzhala et al, , 2010Nardou et al, 2009) and in human neonates (Kahle et al, 2009).…”
Section: Gaba a Receptor-mediated Depolarizing Actionsmentioning
confidence: 92%
“…Fifth, HCO 3 − dependent depolarization may lead to the activation of voltage-gated Ca 2+ channels (Autere et al, 1999). In line with this view, it has been reported that antiepileptic drugs such as topiramate inhibit the cytosolic carbonic anhydrase (Dodgson et al, 2000) thus decreasing or abolishing GABA A receptor-mediated depolarizing responses (Herrero et al, 2002). In addition, it has been proposed that inhibiting NKCC1 with bumetanide can reduce and even abolish seizures in rodent models of neonatal seizures (Dzhala et al, 2005(Dzhala et al, , 2010Nardou et al, 2009) and in human neonates (Kahle et al, 2009).…”
Section: Gaba a Receptor-mediated Depolarizing Actionsmentioning
confidence: 92%
“…32 Topiramate's enhancement of gamma-aminobutyric acid (GABA)-mediated chloride fluxes, 34 blockade of kainateinduced fluxes, 35 and state-dependent blockade of Na þ channels 36 appear relevant to its antiseizure activity, but bear no obvious relationship to appetite or weight loss. Topiramate is also a weak inhibitor of carbonic anhydrase, especially isoenzymes II and IV, 37 which presumably accounts for its frequent induction of paraesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Two more recently introduced AEDs, zonisamide and topiramate, also inhibit carbonic anhydrase, which may contribute to their side effects, including kidney stones and perhaps also oligohydrosis and hyperthermia. 392,393 The action of topiramate on carbonic anhydrase has been assumed not to contribute to its clinical efficacy, because cross-tolerance to the anticonvulsant activity of topiramate does not occur with acetazolamide in mice. 394 However, a recent study finds closely comparable potency for acetazolamide and the two AEDs against cytosolic carbonic anydrase isozyme II and mitochondrial carbonic anhydrase isozyme V. 395 Carbonic anhydrase is a zinc-containing enzyme that is inhibited by interaction of sulfonamide or sulfamate compounds with the Zn(II) ion and specific residues of the protein.…”
Section: Carbonic Anhydrasementioning
confidence: 99%